Effect of Bay Leaf Extract (Syzygium polyanthum) on The Histopathological Appearance of Large Intestine of White Rats (Rattus novergicus) Induced by Ibuprofen - Patrick David Altissimo Balbesi; Efrisca M. Br. Damanik; Sangguana Marthen Jacobus Koamesah; Regina M. Hutasoit (Jurnal Biologi Tropis, 2026)
Nonsteroidal anti-inflammatory drugs (NSAIDs), particularly Ibuprofen, are widely used for their analgesic and anti-inflammatory properties. However, irrational or prolonged use may lead to gastrointestinal injury, including NSAID-induced colitis, due to the inhibition of protective prostaglandins in the mucosa. Syzygium polyanthum (bay leaf) extract contains flavonoids, tannins, saponins, and essential oils with antioxidant and anti-inflammatory properties, making it a potential agent for improving mucosal damage in the colon. Objective to determine the effect of bay leaf (Syzygium polyanthum) extract on the histopathological features of the colon in Sprague Dawley rats induced with Ibuprofen. This study was an experimental laboratory research using a posttest-only control group design. Thirty male Sprague Histopathological assessment of the colon was performed across five fields of view using the scoring system. Data were analyzed using the Kruskal–Wallis test followed by the Mann–Whitney test. The positive control group exhibited severe mucosal damage with extensive epithelial erosion and inflammatory infiltration. The P1 group (50 mg/kgBW) showed moderate improvements, while the P2 group (150 mg/kgBW) demonstrated reduced inflammation and ulceration. The highest dose group, P3 (250 mg/kgBW), showed the most prominent mucosal recovery, with significantly milder lesions compared to other groups. Bay leaf extract significantly improves the histopathological condition of the colon in Ibuprofen-induced rats. Higher doses of the extract result in better mucosal healing and reduced tissue damage.